2015
DOI: 10.1016/j.fuel.2015.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Combustion and pyrolysis reactions of alkylated polycyclic aromatic compounds: The decomposition of 13C methylarenes in relation to diesel engine emissions

Abstract: The thermal decomposition of methylarenes labelled with 13 C in the methyl group was investigated. This was conducted using both a direct injection diesel engine and a pyrolysis flow cell connected to a GC-MS. 2- methylphenanthrene in the fuel a significant amount was retained in the particulate, even though the principal in-cylinder reaction was dealkylation. Pyrolytic reactions of the 13 Clabelled methyl arenes were studied in a micro-pyrolysis-GC-MS-apparatus and confirmed dealkylation as the predominant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…A number of other methylated-PAHs were detectable including 1-13 C-and 2-13 C-methylnaphthalenes, with the 13 C label shown to reside in the methyl position, suggesting that re-alkylation of pyrolysis-formed PAHs occurred. Follow-up work investigated the decomposition of methylnaphthalene and methylphenanthrene in a compression ignition engine and a flow cell reactor (Lea-Langton et al, 2015). Similar results were obtained in both systems, which showed that dealkylation was the predominant reaction.…”
Section: Pahsmentioning
confidence: 63%
“…A number of other methylated-PAHs were detectable including 1-13 C-and 2-13 C-methylnaphthalenes, with the 13 C label shown to reside in the methyl position, suggesting that re-alkylation of pyrolysis-formed PAHs occurred. Follow-up work investigated the decomposition of methylnaphthalene and methylphenanthrene in a compression ignition engine and a flow cell reactor (Lea-Langton et al, 2015). Similar results were obtained in both systems, which showed that dealkylation was the predominant reaction.…”
Section: Pahsmentioning
confidence: 63%
“…The release of methane occurs from around 450 °C up to 750 °C, exhibiting two peaks, which consist of a sharp one reached at around 500 °C and a shoulder peak at higher temperature ranges. , Methane is expected to be the most abundant species by weight in gases, and it is mainly derived from C–C cleavages of cycloalkanes and alkyl side chains linked to naphthenic and aromatic moieties. At temperatures higher than 650 °C, the formation of methane is attributed to cleavage of strongly bound aryl–methyl . The evolution profile of ethylene covers a wide temperature range from 400 to 800 °C, with the sharpest peak at around 520 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was reported that dealkylation of (m)ethylated naphthalenes occurs during thermal degradation, which is supported by model studies on 13 C-labelled methyl arenes. 37 In the presence of a zeolite, the BTX formed by catalytic aromatization of PAH-derived products most likely originates from the alkyl chains of substituted higher aromatics present in the PAH fraction. 36 The catalytic pyrolysis of the PCA fraction produced a biooil in 77 wt% yield on feed, together with water (12 wt%), residual solids (1.3 wt%), and gas (2.3 wt%) (mass balance closure of 93%) (Fig.…”
Section: Resultsmentioning
confidence: 99%